Synthesis and biological evaluation of N4‐hydrazone derivatives of 5, 7‐dihydro‐6H‐pyrrolo[2, 3‐d]pyrimidin‐6‐one as novel anticancer agents with antimetastatic adjunct efficacy. Issue 11 (8th August 2021) - Zhao, Zhichang; Wang, Hongjun; Tian, Nana; Yan, Hong; Wang, Juan
Abstract: To obtain new anticancer agents with antimetastatic adjunct efficacy, a series of novel N 4 ‐hydrazone derivatives of 5, 7‐dihydro‐6 H ‐pyrrolo[2, 3‐ d ]pyrimidin‐6‐one were designed and synthesized by an eight‐step reaction, with appropriate yields. All the synthesized compounds were evaluated for their antiproliferative activity against A549 and MCF‐7 cells and for antiplatelet aggregation activity in vitro. The results showed that compounds 25 and 35 not only showed potent antiproliferative activity against the A549 (IC50  = 15.3 and 21.4 μM) and MCF‐7 (IC50  = 15.6 and 10.9 μM) cell lines but also showed certain antiplatelet aggregation activity (inhibition rates: 47.0% and 45.8%). These results indicated that the structural modification on the N 4 ‐hydrazone moiety of 5, 7‐dihydro‐6 H ‐pyrrolo[2, 3‐ d ]pyrimidin‐6‐one is promising to obtain novel anticancer compounds with antimetastatic adjunct efficacy. In addition, a molecular docking study was performed to investigate the possible targets, and these results indicated that compounds 25 and 35 have the potential to target EGFR, HER2, and P2Y12 . Abstract : Novel N 4 ‐hydrazone derivatives of 5, 7‐dihydro‐6 H ‐pyrrolo[2, 3‐ d ]pyrimidin‐6‐one were designed, synthesized, and tested for their antiproliferative and antiplatelet aggregation activities in vitro. Compounds 25 and 35 showed potent antiproliferative activity against A549 and MCF‐7 cells and some antiplatelet aggregation activity (47.0% and 45.8% inhibition). Molecular docking showed that compounds 25 and 35 can target EGFR, HER2, and P2Y12 .